Critérios para o tratamento jurídico-penal do índio - Rezende, Guilherme Madi (2005)
The aim of this dissertation is to verify whether the non-imputability criterion adopted for the legal penal treatment of Brazilian Indians is the best option available or whether there are other criteria which may be applied more appropriately in this case. For such purpose, this dissertation starts by examining the concept of being an Indian, which is analyzed with basis on a brief description of the cultural differences common to the various Brazilian Indian peoples, but which contrast with the cultural standards of the other members of Brazilian society. Next, the dissertation traces a historical account of the legal treatment given to Brazilian Indians in Colonial, Imperial and Republican Brazil, which extends to the present time to mention two different aspects: the right of Indian peoples to a jurisdiction of their own and, more particularly, the non-imputability criterion adopted by Brazilian law for the penal treatment of Indian people. This work refers to the Bill under procedure at the House of Representatives. There is also reference to Brazilian jurisprudence by means of a non-systematic sample of the judgments concerning the matter. In the next topic, the dissertation discusses the different criteria proposed by the doctrine for the legal penal treatment of Indian people, specially the criteria of nonimputability, of the individualization of the sentence __ specifically considering the fact 9 that the agent is a native Brazilian __ and the criterion of the culturally conditioned. mistake of law Comparative Jurisprudence is addressed based on the analysis of the Penal Codes of some Latin American countries, with special attention to Peru, Bolivia, Colombia and Mexico, which present specific provisions concerning Indian people. After that, the dissertation studies the non-imputability criteria, starting with a brief description of criminal imputability, mistake and culturally conditioned mistake. At the end, based on the premise that founds the doctrine of culturally conditioned mistake, this dissertation proposes as a possible solution the penal treatment of indigenous people through an eventual exculpatory cause, the non-requirement of diverse conduct, whenever one cannot require from the native Brazilians, due to their already internalized cultural values, in a concrete case, to act in accordance with the violated criminal law.